Industrial air pollution and lung and bronchus cancer survival in New Mexico, USA - Xi Gong; Yanhong Huang; Charles L. Wiggins; Angela L. W. Meisner; Yan Lin; Li Luo (Cancer Causes & Control, 2026)
Purpose Lung and bronchus cancer (LBC) is the leading cause of cancer-related deaths. This study examines the relationship between exposure to industrial air pollution and lung and bronchus cancer survival (LBCS) in New Mexico, USA, from 1990 to 2019. Methods This retrospective cohort study included data from 18, 273 lung and bronchus cancer patients. Residential exposure to nine industrial air pollutants was estimated for each patient using the Emission Weighted Proximity Model (EWPM), which integrates industrial air emission data and air quality monitoring data form the U.S. Environmental Protection Agency’s (EPA). Cox proportional hazards modeling was applied to identify industrial air pollutants as decreased LBCS risk factors, adjusting for age at diagnosis, gender, cancer stage, race/ethnicity, smoking prevalence, and urbanization of residential address. Results Results show that residential exposure to 1,1,1-trichloroethane and cobalt during the survival period was significantly associated with decreased LBCS (adjusted hazard ratio [adjHR] for 1,1,1-trichloroethane: 1.06, 95% CI: 1.04, 1.09 and adjHR for cobalt: 1.06, 95% CI: 1.03, 1.09) compared to those unexposed among all patients. When exposure levels were categorized into four groups (unexposed, low, medium, high) based on annual average exposure during the survival period, the associations remained consistent. Conclusion This study underscores the negative influence of industrial air pollution on LBCS and emphasizes the need for targeted public health interventions in high-exposure areas.